Learning data modeling - Blaha, Michael (Infinite Skills, 2014)
"In this Learning Data Modeling training course, expert author Michael Blaha will teach you how to build data models, as well as prepare a data model for simple problems. This course is designed for users that have some programming experience, however, no data modeling experience is needed. You will start by learning about the data modeling development process, then jump into basic and advanced data modeling. From there, Michael will teach you how to create a UML data model, including finding classes, adding attributes, and simplifying the model. This video tutorial also covers how to translate a UML data model into an IE data model, model quality, the different kinds of data models, and database design. You will also learn how to create an SQL server database, an MS-Access database, and develop frameworks. Finally, Michael will teach you about data modeling patterns and database reverse engineering."--Resource description page.